Myocardial stress after competitive exercise in professional road cyclists - König, D.; Schumacher, Y. O.; Heinrich, L.; Schmid, A.; Berg, A.; Dickhuth, H. H. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: Based on the determination of cardiac troponin (cTnT), brain natriuretic peptide (BNP), and echocardiographic measurements, recent investigations have reported myocardial damage and reversible cardiac dysfunction after prolonged endurance exercise in apparently healthy subjects. In the present study, we investigated the myocardial stress reaction in professional endurance athletes after strenuous competitive physical exercise. METHODS: Eleven highly trained male professional road cyclists (age 27 +/- 4 yr; .VO2peak 67 +/- 5 mL.kg-1.min-1; training workload 34,000 +/- 2,500 km.yr-1) were examined. The following parameters were determined before and after one stage of a 5-d professional cycling race: BNP, cTnT (third-generation assay that shows no cross reactivity with skeletal TnT), creatine kinase (CK), creatine kinase MB (CKMB), myoglobin (Myo), and urea. All participants were submitted to a careful cardiac examination including echocardiography and stress ECG. RESULTS: None of the athletes showed pathological findings in the cardiac examination. CK (P < 0.01), CKMB (P < 0.05), and Myo (P < 0.01) were increased after the race. Normal postexercise cTnT levels indicate that the increase in CK, CKMB, and Myo was of noncardiac origin. In contrast, BNP rose significantly from 47.5 +/- 37.5 to 75.3 +/- 55.3 pg.mL-1 (P < 0.01). Pre- and postexercise values of BNP as well as the individual exercise-induced increase in BNP were significantly correlated with age (R2 = 0.68, R2 = 0.66, and R2 = 0.58, respectively; P < 0.05). CONCLUSION: Strenuous endurance exercise in professional road cyclists does not result in structural myocardial damage. The rise in BNP in older athletes may reflect a reversible, mainly diastolic left ventricular dysfunction. This needs to be confirmed by larger trials including different intensities, sports, and age groups.